17 Β-Estradiol Oxidative Stress Attenuation And Autophagy-Induced Dopaminergic Neuroprotection - Roya Varmazyar; Ali Noori-Zadeh; Farzad Rajaei; Shahram Darabi; Salar Bakhtiyari (Cell Journal, 2018)
Objective Degeneration of dopaminergic neurons in the substantia nigra of the brain stem is the main pathological aspect of Parkinson’s disease (PD). 17 β-estradiol (E2) has neuroprotective effects on substantia nigra, however, the underlined mechanism is not well-known. In this study, we evaluated the neuroprotective effects of E2 in the ovariectomized 6-hydroxydopamine- (6-OHDA) rat model of PD.